There and back again: Oocephalus piranii is better treated as Hyptis (Hyptidinae, Lamiaceae) - Soares, Arthur De Souza; Harley, Raymond Mervyn; Barêa Pastore, José Floriano; Gomes Jardim, Jomar (Phytotaxa, 2022)
Hyptis piranii, an endemic species from campos rupestres of Minas Gerais state, Brazil, was described as a member of H. sect. Polydesmia subsect. Oocephalus. After a number of sections and subsections of Hyptis had been raised to generic rank, this species became a member of the genus Oocephalus. Recent morphological analyses showed that, actually, the species is better treated as a member of Hyptis sect. Eriosphaeria. We provide a description of Hyptis piranii, as well as comments on its morphology and a plate showing key morphological features.